Diametral theory of algebraic surfaces and geometric theory of invariants of groups generated by reflections. I - Ignatenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
A review of the current state of the diametral theory of algebraic hypersurfaces in the real Euclidean space is given.